KOMUNIKASI PEMERINTAH DAERAH DALAM PEMASARAN OBJEK PARIWISATA DI KABUPATEN SIAK TAHUN 2016-2017 - ", Rolina; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The importance of local government communication in tourism marketing is to promote the potential of tourism objects in Siak district to attract the attention of tourists both foreign tourists and local tourists, in order to get to know the various types of tourist objects that can be found and visited in the Siak regency. This study aims to determine the communication of local government in marketing tourism objects in Siak districts in 2016-2017. The location of this research was conducted in Siak City, Siak Regency. Data collection techniques are carried out by interview and documentation. The method used in this study is descriptive qualitative. The results of the study revealed that local government in marketing of tourism objects in Siak districts in 2016-2017 had not run optimally. in 2016 the tourism agency, youth and sports had not made good cooperation with the private sector and local communities in conducting communication and outreach to carry out information dissemination activities on the potential of the tourism objects in Siak district. in 2017 the district government of Siak is involved in supporting every activity carried out by the tourism agency to make the people who live close to the location of tourist attractions as local tour guides. Each community is given training and counseling to give its role and participation in supporting tourism marketing activities carried out in Siak district. As for 5 (five) elements of local government communication in marketing tourism objects in Siak Regency, namely: communicator, message, communicant, media or chanel, and effect (influence). Keywords: communicator, message, communicant, media or chanel, effect